Resilient Tourism : Competitiveness in the Face of Disasters - World Bank (World Bank, Washington, DC, 2020)
Enhancing Competitiveness in the Face of Disasters presents the case to government decision-makers, tourism private sector stakeholders, and development partners that the industry must act urgently to integrate resilience as a core component of its competitiveness agenda. Its objectives are to: build knowledge of how and why the tourism sector is vulnerable to disaster and climate risks; raise awareness of disaster and climate impacts on tourism competitiveness; examine barriers to proactive mitigation and risk-informed decision-making; and present examples of approaches in different countries. The report flags the need for research and methodology in this emerging field and proposes a Resilient Tourism Framework to integrate preparedness, response, and recovery actions into the sector. This report is part of a series under the World Bank’s Resilient Industries Program, which proposes ways to integrate disaster and climate resilience considerations into the industrial development investment projects the World Bank supports. Its flagship report, Resilient Industries: Competitiveness in the Face of Disaster, details a Resilient Industries Framework which informs the Resilient Tourism Framework.